Contamination of Toxic Heavy Metal in Locally Made Plastic Food Packaging Containers (Global Journal of Science Frontier Research, 2015)
Human exposure to toxic heavy metals creates a major health hazards. The main objectives of our study was to examine the concentration of toxic heavy metals like Lead (Pb), Copper(Cu), Nickel(Ni), Zinc(Zn), Manganese(Mn), Chromium(Cr) and Cadmium(Cd) in locally made food containers purchased from various districts of U.P (India). All samples are analyzed at 60±2°C for 2hrs in different simulating solvents as per BIS, IP, USP and other guidelines by using atomic absorption spectrophotometer(AAS). The results shows that leaching of heavy metals occur in all samples and follows the order: Pb(1.9-0.0001 ppm) > Cu(1.61-0.0001 ppm) >Ni(1.31-0.001 ppm) > Zn(1.02 -0.001 ppm) > Mn(1.01-0.0001 ppm) > Cr(0.14-0.0001 ppm) > Cd(0.01-0.0001 ppm).
Keywords: food containers; concentrations; heavy metals; toxic; health; plastic